A holistic understanding of the emotional experience of festival attendees. (19th May 2022) - Rodríguez-Campo, Lorena; Alén-González, Elisa; Antonio Fraiz-Brea, José; Louredo-Lorenzo, Montserrat
Abstract: Consumer behavior models in recent years have been strongly influenced by the predictive power of emotions. This has resulted in an increasing tendency to include them in the construction of overall global models. In parallel, theories extracted from positive psychology have begun to be applied to the planning and management of events. This article has a two-fold objective: to measure the emotions experienced in situ by the attendees to the 10th Vilalba International Festival (Galicia, Spain) and to identify the role played by emotions, social identification, and satisfaction in visitors' behavioral intentions. The study is based on a survey of 317 attendees to the festival. Satisfaction has proven to be the main determinant of visitors' re-attendance and postvisit recommendation behavior. Joy was the most intense, basic, positive emotion reported by attendees, followed by love. This led to their social identification with other participants and to a feeling of satisfaction with the festival.